Does environmental regulation enhance firm's position in dual value chain? An analysis based on environmental information disclosure. (1st November 2022) - Zou, Han; Zhong, Mei-Rui
Abstract: Climbing the dual value chain (DVC) of parallel development in global and domestic value chains is an important channel to get rid of bottom solidification. Based on the data of international input-output tables after embedding provinces and decomposing value-added flow during 2003–2012, this article provides measurement for downstream or upstream embedding and division position indexes of A-listed firms. Then, theoretical framework of environmental regulation affecting DVC embeddedness is constructed, and the Environmental Information Disclosure (EID) trial implemented in 2008 is regarded as a quasi-natural experiment. The results show that EID enhances corporate division position in DVC by weakening downstream embeddedness and increasing upstream embeddedness, domestic firms are gradually transforming from low-end manufacturers to high-end designers. The effect works with a year lag in downstream embeddedness and lags 2 years in others. Heterogeneity analysis confirms that enhancement of division position is more sensitive in resource-rich cities with high marketization or labor-intensive firms and manufacturing or service sectors. Besides, we find that environmental regulation such as EID induces technological innovation for process upgrade, product improvement for quality upgrade and allocation optimization for function upgrade to transform the role and degree of firms embedding DVC. Highlights: Boundary delimitation of DVC at both theoretical and empirical levels. A theoretical framework about the effects of environmental regulation on DVC. Environmental regulation improves the division position of corporate embedding DVC. It works better in resource-rich, market-oriented cities or labor-intensive firms. Transmission pathways are realized by technology, structure and allocation effects.